2019
DOI: 10.1103/physrevlett.122.048101
|View full text |Cite
|
Sign up to set email alerts
|

Front Instabilities Can Reverse Desertification

Abstract: Degradation processes in living systems often take place gradually by front propagation. An important context of such processes is loss of biological productivity in drylands or desertification. Using a drylandvegetation model, we analyze the stability and dynamics of desertification fronts, identify linear and nonlinear front instabilities, and highlight the significance of these instabilities in inducing self-recovery. The results are based on the derivation and analysis of a universal amplitude equation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…In that range we consider precipitation values below the Maxwell point, where desertification fronts exist (bare soil displacing uniform vegetation). In the vicinity of the bare-soil instability to uniform vegetation (P = P C in Figure 4) the two-variable model presented in Appendix B can be reduced to an amplitude equation for the uniform mode that begins to grow at this instability [85]. Analysis of this equation reveals a transverse front instability [86,87], whereby small bulges along the front line are first enhanced, then develop into growing fingers that avoid one another, and ultimately fill up the system domain with a stationary labyrinthine pattern.…”
Section: Front Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that range we consider precipitation values below the Maxwell point, where desertification fronts exist (bare soil displacing uniform vegetation). In the vicinity of the bare-soil instability to uniform vegetation (P = P C in Figure 4) the two-variable model presented in Appendix B can be reduced to an amplitude equation for the uniform mode that begins to grow at this instability [85]. Analysis of this equation reveals a transverse front instability [86,87], whereby small bulges along the front line are first enhanced, then develop into growing fingers that avoid one another, and ultimately fill up the system domain with a stationary labyrinthine pattern.…”
Section: Front Dynamicsmentioning
confidence: 99%
“…According to the analysis of the amplitude equation, the instability occurs as the soil-water diffusion coefficient, D W , exceeds a threshold value, and that threshold is inversely related to the root-to-shoot ratio, E, which controls water uptake by plants' roots [85]. This result uncovers the mechanism of the instability-fast soil-water diffusion (relative to biomass expansion) towards incidental bulges along the front line that locally deplete the soil-water content.…”
Section: Front Dynamicsmentioning
confidence: 99%
“…Of exceptional interest may be the study of the higher-dimensional lattice, as exciting pattern formation dynamics may emerge due to the interplay of discreteness and higher-dimensionality, see [25,42]. Another interesting direction is leading to the study of relevant coupled lattice systems [24,25,[43][44][45]. Studies revolving around the above themes are in progress and will be reported in future works.…”
Section: Discussionmentioning
confidence: 99%
“…An important, yet incomplete issue, concerns a detailed bifurcation analysis for the emergence of the aforementioned spatial-inhomogeneous states and the potential detection of snaking effects [39][40][41]. Of exceptional interest may be the study of the higher-dimensional lattice, as exciting pattern formation dynamics may emerge due to the interplay of discreteness and higher-dimensionality, see [25,42]. Another interesting direction is leading to the study of relevant coupled lattice systems [24,25,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation